The Murine Factor H-Related Protein FHR-B Promotes Complement Activation - Cserhalmi, Marcell; Csincsi, Ádám I.; Mezei, Zoltán; Kopp, Anne; Hebecker, Mario; Uzonyi, Barbara; Józsi, Mihály (Frontiers in Immunology, 2017)
Factor H-related (FHR) proteins consist of varying number of complement control protein domains that display various degrees of sequence identity to respective domains of the alternative pathway complement inhibitor factor H. While such FHR proteins are described in several species, only human FHRs were functionally investigated. Their biological role is still poorly understood and in part controversial. Recent studies on some of the human FHRs strongly suggest a role for FHRs in enhancing complement activation via competing with factor H for binding to certain ligands and surfaces. The aim of the current study was the functional characterization of a murine FHR, FHR-B. To this end, FHR-B was expressed in recombinant form. Recombinant FHR-B bound to human C3b and was able to compete with human factor H for C3b binding. FHR-B supported the assembly of functionally active C3bBb alternative pathway C3 convertase via its interaction with C3b. This activity was confirmed by demonstrating C3 activation in murine serum. In addition, FHR-B bound to murine pentraxin 3 (PTX3), and this interaction resulted in murine C3 fragment deposition due to enhanced complement activation in mouse serum. FHR-B also induced C3 deposition on C-reactive protein (CRP), the extracellular matrix extract Matrigel, and endothelial cell-derived extracellular matrix when exposed to mouse serum. Moreover, mouse C3 deposition was strongly enhanced on necrotic Jurkat T cells and the mouse B cell line A20 by FHR-B. FHR-B also induced lysis of sheep erythrocytes when incubated in mouse serum with FHR-B added in excess. Altogether, these data demonstrate that, similar to human FHR-1 and FHR-5, mouse FHR-B modulates complement activity by promoting complement activation via interaction with C3b and via competition with murine factor H.